Steady-State Labor Supply Elasticities: A Survey - Olivier Bargain; Andreas Peichl (Institute for the Study of Labor (IZA), 2013)
Previous reviews of static labor supply estimations concentrate mainly on the evidence from the 1980s and 1990s, Anglo-Saxon countries and early generations of labor supply modeling. This paper provides a fresh characterization of steady-state labor supply elasticities for Western Europe and the US. We also investigate the relative contribution of different methodological choices in explaining the large variation in elasticity size observed across studies. While some recent studies show that genuine preference heterogeneity across countries explains only a modest share of this variation (Bargain et al., 2013), we focus here on time changes and estimation methods as key contributors of the differences across studies. Both factors can explain larger elasticities in older studies (i.e. an increase in female labor market attachment over time and a switch from the Hausman estimation approach to discrete-choice models with tax-benefit simulations). Meta-analysis evidence suggests that smaller elasticities in the recent period may be due to the time factor, i.e. a likely change in work preferences, both in the US and in Europe.
Keywords: C25; C52; H31; J22; 330; household labor supply; elasticity; taxation; Europe; US